Ekspresi Budaya Membangun pada Masyarakat Jeron Beteng, Kecamatan Kraton, Yogyakarta - Endy Marlina; Arya Ronald (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
The society has culture which influencing their habitat which can reveal a culture that underlies their daily life. The aims of this research is to reveal the expression of culture of build the architecture work of society. This topic related to six aspects, they are geography, ideology, personality, belief, social bond, and meaning. They influence the way of thinking, attitude, and cultural creation. This research found the shift and continuity of culture within society which explored based on the changes of the architecture.